Analysis of Patient Satisfaction with Service Quality at the West Lombok Regional General Hospital (RSUD) - Nasrullah, Nasrullah; Karno, Darma; Jayusman, Iqbal Sadjali (Asosiasi Dosen Muda Indonesia, 2025)
Patient satisfaction is an important indicator in assessing the quality of healthcare services in hospitals. This study aims to analyze the level of patient satisfaction with the quality of services at the West Lombok Regional General Hospital. Aspects analyzed include reliability, responsiveness, assurance, empathy, and tangibles. This study used a cross-sectional design, with a population of 5,362 respondents, with a sample of 99 visiting respondents. The sampling method in this study was purposive sampling. This study was conducted from June 2 to June 10, 2022. Data collection and retrieval used a questionnaire. The results of statistical analysis using the Chi-Square statistical test and logistic regression showed a significant relationship (p-value <0.05) for the responsiveness variable (p-value 0.032) and tangible (p-value 0.000). The results of multivariate statistical tests showed that the dominant factor influencing patient satisfaction with services was tangible (p=0.000; OR=18.631). Hospitals are expected to improve the comfort of inpatient rooms by paying attention to lighting, cleanliness of rooms, bathrooms, and the completeness and availability of equipment.